Artificial intelligence-based design of assemblies in the FreeCAD software - Wdowik, Roman; Bełzo, Artur (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2025)
The article presents application of the FreeCAD software and generative artificial intelligence (AI) in the design process regarding exemplary mechanical engineering-related assemblies. Authors have studied how to support a product development and computer-aided (CAD) design phase by the use of generative pre-trained transformer (GPT). Prompting process, that lead to Python language-based code creation in the ChatGPTTM by OpenAI company, was studied from the perspective of 3D assemblies generation in the FreeCAD software. Moreover, authors studied how to improve the basic 3D models by the use of text-based prompts and CAD user improvements of the solid models and discussed the general effectiveness of this approach. It was also separately studied how to automate creation of many parts of the same type by the use of the AI, and apply such CAD libraries in the developed assemblies. The performed research presented selected possibilities of AI-based design process, challenges of the design process and future areas of investigation of AI-based assembly development resulting from the usage of existing GPTs.